A Pedagogical Model of Strategic Management. Part 2 (GESTIÓN Y TENDENCIAS, 2024)
Strategic management is a fundamental pillar of long-term business competitiveness and sustainability. This article presents a practical framework for designing "strategic definitions" —purpose, mission, vision, and values— as essential components that give meaning and direction to organizational activity. Through a pedagogical proposal, the authors set out a cyclical six-step process ranging from initial reflection and foresight analysis to the integration of these definitions into day-to-day management. The paper stresses that these statements are not decorative elements but critical tools for aligning internal efforts and strengthening identity before stakeholders in a competitive environment.
Keywords: strategic management; mission and vision; organizational purpose; competitive advantage; strategic planning